Iconographic Studies Poster of the Exhibition and Night Market of the Dutch East Indies and Europe, 1930s Colonial Period - Baskoro Suryo Banindro; Listia Natadjaja; Nina Hansopaheluwakan Edward (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2025)
Abstract: This study analyses Art Deco (1930s) colonial exhibition posters from the Dutch East Indies and Europe to uncover their active role as an instrument of visual hegemony that transcends the discourse of exoticism. Through a critical comparative iconography approach (Panofsky's adaptation) reinforced by postcolonial theory (Said, 1978) and representation (Hall), the research reveals how Art Deco syntax, rigid geometry, machine typography, and modern chromaticism are used to transform colonial violence into